Magnetic structure and Dzyaloshinskii-Moriya interaction in the S= 12 helical-honeycomb antiferromagnet α-Cu2 V2 O7 - G. Gitgeatpong (2018)
© 2015 American Physical Society. ©2015 American Physical Society. au. Magnetic properties of the S=12 antiferromagnet α-Cu2V2O7 have been studied using magnetization, quantum Monte Carlo (QMC) simulations, and neutron diffraction. Magnetic susceptibility shows a broad peak at ∼50K followed by an abrupt increase indicative of a phase transition to a magnetically ordered state at TN=33.4(1) K. Above TN, a fit to the Curie-Weiss law gives a Curie-Weiss temperature of Θ=-73(1) K suggesting the dominant antiferromagnetic coupling. The result of the QMC calculations on the helical-honeycomb spin network with two antiferromagnetic exchange interactions J1 and J2 provides a better fit to the susceptibility than the previously proposed spin-chain model. Two sets of the coupling parameters J1:J2=1:0.45 with J1=5.79(1) meV and 0.65:1 with J2=6.31(1) meV yield equally good fits down to ∼TN. Below TN, weak ferromagnetism due to spin canting is observed. The canting is caused by the Dzyaloshinskii-Moriya interaction with an estimated bc-plane component Dp≃0.14J1. Neutron diffraction reveals that the S=12Cu2+ spins antiferromagnetically align in the Fd′d′2 magnetic space group. The ordered moment of 0.93(9) μB is predominantly along the crystallographic a axis.